2011
DOI: 10.1113/expphysiol.2011.058172
|View full text |Cite
|
Sign up to set email alerts
|

Liver glutathione S-transferase α expression is decreased by 3,5,3′-triiodothyronine in hypothyroid but not in euthyroid mice

Abstract: As previously reported, the activity of liver glutathione S-transferases, an important family of enzymes for detoxification processes, is regulated by thyroid hormone levels. Here, we specifically studied glutathione S-transferase α (Gsta) gene expression in livers of mice. First, in wild-type (WT) mice, hypothyroidism was induced by 5 weeks of a diet containing 5-propyl-2-thiouracil plus water containing metimazole, whereas hyperthyroidism was induced by daily injections of 50 μg (100 g body weight)−1 of 3,3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
3
12
0
Order By: Relevance
“…The total serum T 3 levels of male and female TR␤ ⌬337T/⌬337T mice were similar and five to seven times higher compared with wild-type animals, as reported before (20,50). The TR␤ ⌬337T/⌬337T mouse is a model in which T 3 , even when present in high levels, is unable to bind to TR␤.…”
Section: Resultssupporting
confidence: 50%
See 4 more Smart Citations
“…The total serum T 3 levels of male and female TR␤ ⌬337T/⌬337T mice were similar and five to seven times higher compared with wild-type animals, as reported before (20,50). The TR␤ ⌬337T/⌬337T mouse is a model in which T 3 , even when present in high levels, is unable to bind to TR␤.…”
Section: Resultssupporting
confidence: 50%
“…Recent data from our group have shown that liver GST␣ is inhibited by T 3 in a hypothyroid state but not when mice are euthyroid (EU). This finding was dependent on the cooperative actions of the two different TH receptor isoforms, TR␣1 and TR␤1 (20).…”
mentioning
confidence: 88%
See 3 more Smart Citations